The effects of nutrient uniformity and modified feed processing on animal performance - Clark, Patrick M. (Kansas State University, 2006)
A series of experiments were conducted evaluating the effects of marker selection and mix time on feed uniformity, feed uniformity on animal performance, and the addition of cracked corn to a concentrate pellet on broiler performance. Utilizing a common corn-soybean meal based poultry diet, as mix time increased, there was an overall decrease in % Coefficient of Variation (CV) observed, which was independent of which marker was used. Crude protein should be considered to be an inferior marker as several ingredients in the batch contribute some level of protein and overall decreased numerically less than 1% CV. Synthetic amino acids (methionine and lysine) prevailed as the most consistent markers reducing in magnitude by 60.32% and 55.97% (methionine and lysine, respectively). To evaluate the effects of feed uniformity on broiler performance, as determined by CV, methionine was added to a basal diet and mixed for 10, 20, 30, 40, or 120-s, with methionine being the only ingredient varying. During the starter period (d 0 to 16) ADG increased significantly (quadratic P<0.001) as well as F:G (quadratic P<0.001). However, in overall (d 0 to 41) growth performance only ADG improved (quadratic P<.001). Average daily feed intake appeared to be a contributing factor in growth performance for all stages of growth. Cracked corn was added to a concentrated pellet to evaluate growth performance on broilers and potential cost reductions at the feed manufacturing facility. A linear decrease was observed overall (0 to 41 d) for ADG, ADFI, and F:G (P<0.003, respectively). Gizzard weight and gizzard yield were significantly increased (P<0.043 and P<0.008, respectively) as cracked corn level increased.
Keywords: Feed Manufacturing; Diet Uniformity; Agriculture, Animal Culture and Nutrition (0475)